INDOSAT CUSTOMER SATISFACTION AND RELATIONSHIP MARKETING - Hardi Fardiansyah; Rio Christiawan (Journal of Management and Creative Business, 2023)
Since customer satisfaction is a prerequisite for establishing customer loyalty, it follows that satisfaction is a factor that fosters customer loyalty. Loyalty must be fostered if producers and customers are to have a positive connection. This study was conducted to investigate the partial and simultaneous effects of relational marketing and customer satisfaction on customer loyalty in the city of Tasikmalaya. With 116 participants, this study used a random sample technique and a causal quantitative design. Additionally, this study uses various linear regression analytic techniques to assess the data. This study found that customer loyalty to Indosat in the city of Tasikmalaya was partially or simultaneously influenced by relational marketing and customer happiness.